Use of venous couplers in microsurgical lower extremity reconstruction: a systematic review and meta-analysis - Haug, Valentin; Panayi, Adriana C.; Kadakia, Nikita; Abdulrazzak, Obada; Endo, Yori; Udeh, Kodi; Kollar, Branislav; Hundeshagen, Gabriel; Pomahac, Bohdan; Kneser, Ulrich; Hirche, Christoph (Microsurgery, 2021)
Background Free tissue transfer for lower limb reconstruction has become a workhorse procedure for limb-salvage. Compared with other recipient sites, the lower extremity has a higher risk of microvascular complications, in particular with venous anastomosis. The study's objective is to evaluate the evidence, safety, and efficacy of venous coupler use in microsurgical anastomosis in lower limb reconstruction to provide objective appraisal of the surgical techniques. Methods A systematic review (SR) and meta-analysis (MA) were performed analyzing articles from PubMed, Cochrane, Embase, and Web of Science from January 1990, to August 2018. Abstracts and titles were screened and assessed for eligibility by independent reviewers. Following full-text review, articles were included in the SR and MA. Case reports were excluded. Cochrane Collaboration and the Quality of Reporting of Meta-analyses (QUOROM) guidelines were followed. Results Out of 15 included studies that met the inclusion criteria for the SR, 9 were included in MA. Patients treated with venous couplers did not experience more surgical complications (risk ratio (RR) 0.79; 95% confidence interval (CI) 0.48-1.33; p = .38), total failure (RR 0.61; 95% CI 0.22-1.70; p = .34), venous compromise (RR 0.72; 95% CI 0.23-2.27; p = .57), arterial compromise (RR 0.85; 95% CI 0.25-2.88; p = .80), partial failure (RR 0.77; 95% CI 0.33-1.77; p = .54), or reoperation (RR 11.79; 95% CI 0.49-286.55; p = .13) in comparison with hand-sewn anastomosis. Conclusions Outcomes of venous couplers in lower limb reconstruction are comparable to those of hand-sewn anastomosis. However, this study was limited by the quality of the available literature. Additional prospective studies should aim to directly compare both techniques and potential further benefits in clinical trials.
First published: 30 March 2020
Gesehen am 12.08.2021